2007
DOI: 10.17348/era.5.0.305-317
|View full text |Cite
|
Sign up to set email alerts
|

The Turnip (<i>Brassica rapa</i> L. subsp. <i>rapa</i>) in Eastern Tyrol (Lienz district; Austria)

Abstract: The turnip (Brassica rapa L. ssp. rapa), has been a very important crop in the Alps for centuries. It's main uses were food and fodder. The fermented turnips (Ruebenkraut) used to be, as was sauerkraut, a very important winter foodstuff. The importance of turnips in Alpine countries is shown by the fact that they were even shown on the coat of arms belonging to noble families. Today, however, only a few remaining farmers still grow and process turnips. These farmers were approached in 1997/98 within an ethnobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Unlike most landraces from Tibet with large bulk tubers (Figure S1), turnips from Japan all have ascending rosettes, smaller taproots, and narrow leaves, and turnips from Europe all have long, slender tubers and deep leaf fissures [51]. Previous studies have reported that the thickened part of turnips consists of both a hypocotyl and a root, and this group was one of the oldest groups of cultivated B. rapa [22,52,53]. Europe and Asia are two different independent origin centers of cultivated B. rapa subspecies [2].…”
Section: Discussionmentioning
confidence: 90%
“…Unlike most landraces from Tibet with large bulk tubers (Figure S1), turnips from Japan all have ascending rosettes, smaller taproots, and narrow leaves, and turnips from Europe all have long, slender tubers and deep leaf fissures [51]. Previous studies have reported that the thickened part of turnips consists of both a hypocotyl and a root, and this group was one of the oldest groups of cultivated B. rapa [22,52,53]. Europe and Asia are two different independent origin centers of cultivated B. rapa subspecies [2].…”
Section: Discussionmentioning
confidence: 90%
“…for cereal cultivation, field vegetables, fibre crops, etc. and the farming of a wide range of domesticated animals, with a low number of individuals per species, were the main components of the subsistence system until the 1960s [ 13 , 17 , 34 ]. Large parts of today’s meadowlands used to be tilled up to an altitude of 1700 m. Farming systems in Eastern Tyrol have undergone change in the past few decades.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding which part of a turnip plant develops into a tuber during the vegetative development is a key for future research investigating this phenomenon. Previous studies often stated that the turnip tuber is a taproot [28] , [35] , [36] , [37] , while a few studies mentioned that the thickened part of turnip consists of both hypocotyl and root [38] , [39] . Our anatomical observations of six genetically diverse turnip accessions showed that turnip tubers are a combination of hypocotyl and root; both organs take part in forming the fleshy organ through secondary growth by a vascular cambium, while the proportion of hypocotyl/root differs among different accessions ( Figure 1 ) and seems to be independent from the geographic origin of the turnip accession.…”
Section: Discussionmentioning
confidence: 99%